On Estimation of Point-in-Time Loss Given Default : A Comparative Study - Kuchta, Michal (2018)
This Thesis deals with the new provisioning standard IFRS9, in the specific case of LGD modelling and proposes a set of robust approaches to meet the Standard's requirements. It compares the scenario generation through conditional forecasting in DSGE with the proposed pioneering methodology endogenizing scenario paths and their probabilities in Bayesian Markov-switching VAR. It develops a range of recovery rate models using survival analysis and principal component regression. Sub-results are then integrated to derive single probability-weighted ECL estimate.